The Effectiveness of the STEM-PjBL Model on the Critical Thinking Ability of Elementary School Students on Natural Resources Materials - Farha Eghita Kamilatun Nuha; Nailah Tresnawati; Tarmidzi (Jurnal Penelitian Pendidikan IPA, 2026)
Elementary school students' critical thinking skills in science learning on the topic of natural resources have not yet developed optimally because instruction tends to rely on conventional Student Worksheets (LKS) and provides limited opportunities for contextual learning. This research sought to evaluate how the STEM-Project Based Learning (STEM-PjBL) model—implemented through a project where students created natural batik dyes—enhances elementary school students' critical thinking skills regarding natural resources. The study adopted a quantitative approach, utilizing a quasi-experimental method structured around a One-Group Pretest–Posttest Design. The sample consisted of 26 fifth-grade students from a public elementary school in Cirebon City, Indonesia, selected through purposive sampling. Data were collected using a critical thinking skills test, a student response questionnaire, and classroom observations. The data were analyzed utilizing the Shapiro–Wilk test, the Wilcoxon Signed Rank Test, N-Gain analysis, and descriptive statistics. The results showed that the mean pretest score increased from 77.02 to 81.54 on the posttest. The Wilcoxon Signed Rank Test demonstrated a statistically significant difference, showing a significance value of 0.001 (p < 0.05), indicating that the model yielded a highly consistent and uniform improvement across the sample. However, the overall N-Gain score was 0.20 (20%), which belongs to the low category, suggesting that while the positive impact of the model was statistically robust, the short-term duration of the intervention limited the total magnitude of the score increase.